Matriline versus patriline: Social mobility in England, 1754-2023 - Gregory Clark; Neil Cummins (European Historical Economics Society (EHES), 2024)
If social outcomes have social causation, mothers and fathers in different societies will have different effects on child outcomes. Social mobility rates on the patriline will differ from that on the matriline. From an extensive family lineage of 426,552 persons in England 1650-2023 we estimate the influence of mothers versus fathers on social outcomes 1754-2023. Mothers' and fathers' education and social status are equally predictive of most child social outcomes across the entire period, even for the patriarchical society of eighteenth-nineteenth century England. Only for wealth was there a much stronger influence of the patriline.
Keywords: J16; J62; 330; Gender and social mobility; mothers versus fathers; gender equality